2018
DOI: 10.1177/0021998318816437
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of microcellulose reinforced polyvinyl alcohol/starch biocomposites

Abstract: This study details about the synthesis of micro-crystalline cellulose prepared from olive pits, the waste material obtained in olive industry, and the effect of these fillers on the tensile and thermal properties of polyvinyl alcohol/starch blends. Micro-crystalline cellulose from olive pits was prepared, and its size was measured using particle size analyzer. Composites were prepared for various micro-crystalline cellulose loading (0, 1, 3, and 5 wt.%) by solution casting method for the blend ratio of 70/30, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…It has been reported that cellulose microfibrils vary in size from 0.2 to 374 µm. The micro-fibrillated cellulose chain aggregates together to form macro-fibrillated chains [43]. However, microcrystalline cellulose has been reported as the non-amorphous region of the chain, which is divided into a well-organized crystal-surface and poorly organised crystal interior [44].…”
Section: Microcellulose Materials Formsmentioning
confidence: 99%
“…It has been reported that cellulose microfibrils vary in size from 0.2 to 374 µm. The micro-fibrillated cellulose chain aggregates together to form macro-fibrillated chains [43]. However, microcrystalline cellulose has been reported as the non-amorphous region of the chain, which is divided into a well-organized crystal-surface and poorly organised crystal interior [44].…”
Section: Microcellulose Materials Formsmentioning
confidence: 99%
“…By the addition of CNC to the PVA/starch matrix, peak representing −OH vibrations were shifted from 3291 to 3306 cm −1 . This indicates the occurrence of hydrogen bonding between CNC and the PVA/starch matrix 39 …”
Section: Resultsmentioning
confidence: 89%
“…The thermoplastic carbon ashes/maize starch (TPAS) films were manually prepared by pre-mixing maize starch neat powders with 35 wt.% of glycerol, respect to the starch matrix and recycled carbon ashes in an amount of 10 phr, 20 phr and 30 phr that correspond to 7 wt.%, 14 wt.% and 21 wt.% [17][18][19][20][21] (see Figure 1). The compounds were mixed at 130 • C for 10 min by using a Haake PolyLab System Rheomix 600/610 mixer (n = 100 rpm) (Haake, Karlsruhe, Germany) and then put in a Carbolite LHT6/120 oven (Carbolite, Derbyshire, UK) until they reached a temperature of 130 • C. Finally, they were compression molded, by means of a DGTS P7/91 press (DGTS, Veduggio (MB), Italy), at a pressure of 70 bar.…”
Section: Preparation Of Thermoplastic Carbon Ashes/maize Starch Filmsmentioning
confidence: 99%
“…Furthermore, Sreekumar P.A. et al obtained microcrystalline cellulose from olive pits (waste material from the olive industry) and used them as a filler of thermoplastic corn starch films and these fillers enhanced the tensile properties [20]. Finally, according to [21], the incorporation of chestnut husks, a lignocellulosic agroforestry waste, in thermoplastic potato starch films can increase the elastic modulus of the samples.…”
Section: Introductionmentioning
confidence: 99%